PELINDUNGAN HUKUM UNTUK PENYEDIA JASA ATAS WANPRESTASI PEMBAYARAN YANG DILAKUKAN OLEH PENGGUNA JASA DALAM PERJANJIAN KERJA KONSTRUKSI - Ahmad Haekal; Felicitas Sri Marniati; Irhamsah, Irhamsah (Journal of Innovation Research and Knowledge, 2025)
Construction work agreements are the basis for legal relations that develop between service providers and service users in the context of construction services, according to Undang-Undang Nomor 2 Tahun 2017 tentang Jasa Konstruksi (UUJK). This relationship is under the scope of civil law, especially agreements. The phenomenon occurs, service users do not pay their obligations to service providers. The problem formulation of this research is how legal responsibility for payment default to service providers in construction work agreements and how is legal protection for service providers for payment default by service users in construction work agreements. The legal theory used in this research is the Agreement Theory from Subekti and the Legal Protection Theory from Satjipto Raharjo. The method used in this research is normative juridical research, specifically library law research or secondary data with primary, secondary and tertiary legal sources. As for the research approach used Statue Approach, Case Approach, Analytical Approach, Conceptual Approach and the method of collecting the legal materials are carried out by identifying and taking an inventory of positive law, journal and other legal sources. The method used in analyzing legal material (interpretation). Grammatically and systemic and legal construction methods. From the research, the right form for service providers of not getting from a service provider is the payment that should be paid by the service user after fulfilling their obligations legal protection can achieve for service providers from valid agreements. A valid agreement will create laws for each party. The rights can be sued.